How ambiguous are climate metrics? And are we prepared to assess and compare the climate impact of new air traffic technologies?. (April 2015) - Grewe, Volker; Dahlmann, Katrin
Highlights: Posing the adequate climate question reduces a large amount of a perceived ambiguity of climate metrics. Five steps are proposed to adequately assess the climate impact of new technologies. Adequate reference, emission scenario, climate indicator, and time horizon can only be deduced from a well-posed question.